Experiences of support by unsuppressed adolescents living with HIV and their caregivers in Windhoek, Namibia: a qualitative study - Munyayi, Farai K.; van Wyk, Brian (Frontiers in Public Health, 2024)
Background Adolescents living with HIV (ALHIV) lag behind younger children and adults in the achievement of HIV care and treatment targets for HIV epidemic control. Treatment outcomes for adolescents may be influenced by their experiences with the support provided in HIV programs. We report on the experiences of virally unsuppressed adolescents and their caregivers with the current support in primary healthcare settings in Namibia. Methods A qualitative descriptive and exploratory study was conducted in 13 public primary healthcare facilities in Windhoek, Namibia. A total of 25 in-depth interviews were conducted with unsuppressed adolescents (n = 14) and their caregivers (n = 11) between August and September 2023. The audio-recorded interviews were transcribed verbatim, and uploaded into ATLAS.ti software, and subjected to thematic content analysis. Findings Three main support domains for the unsuppressed adolescents emerged from our analysis, namely: psychosocial, clinical and care, and socioeconomic support. The psychosocial support was delivered through peer support (teen clubs and treatment supporters) and enhanced adherence counselling mostly. The clinical and care support included implementing adolescent-friendly HIV services, differentiated service delivery approaches, and caregivers and healthcare worker care support for improved ART adherence, clinic attendance and continuous engagement in care. Socioeconomic support was provided for nutritional support, transport to access clinics, and school supplies, as well as income-generating projects. Conclusion Psychosocial, clinical and care, and socioeconomic support are key elements in addressing the needs of adolescents challenged with achieving viral suppression. Health systems may benefit from whole-of-society and whole-of-government approaches to meet the needs of ALHIV that are beyond the scope of health service delivery such as nutritional, education and socioeconomic influences on both the health and well-being of ALHIV.